Soil Health Management Practices in Indian Agricultural System: An Analytical Study of Organic Farmers - BHARDWAJ, RAJNEESH (International Journal of Psychosocial Rehabilitation, 2024)
A large part of India’s economy relies on the work of farmers, who are on average the most common residents of this country. Therefore, any research on the key aspects of agriculture is extremely crucial. Any agricultural land will be unproductive without quality soil that is healthy, fertile, and highly fruitful. Organic farming is a sustainably mindful and environmentally friendly way of farming that promotes the use of natural fertilizers and pest control methods, which can help improve soil quality over time. Additionally, organic produce is often in high demand due to its perceived health benefits and lack of harmful chemicals. For this reason, organic farming is gaining popularity among the common man—both the producers and the consumers. For the producers, the advantages include reduced input costs, improved soil quality and market access, and a reduced carbon footprint. For consumers, an enhanced taste and natural safety are always attractive choices. Moreover, the enlightened consumer might want to inculcate more environmentally sustainable and ethical choices in their life. This paper aims to analyse different soil health management practises, such as organic farming, in the Indian agricultural system.